2023
DOI: 10.1111/ddg.15034
|View full text |Cite
|
Sign up to set email alerts
|

Developments and perspectives in allergology

Abstract: SummaryAllergology is a key part of dermatological care. This paper reviews current pathophysiological, diagnostic and therapeutic developments in immediate‐type allergies.Type‐2 inflammation is involved in several allergological diseases such as allergic rhinitis and asthma. Allergen immunotherapy as an important therapeutic procedure is regulated in Germany by an official legal directive (Therapieallergene‐Verordnung). Therapeutically, several biologics are already available that target interleukin (IL)‐4, ‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…Further research by Hashimoto et al [39] suggested TSLP's involvement in CSU's pruritic symptoms through basophil activation, extending its impact to sensory mechanisms within the disease. Observations by Treudler and Simon [40] on emerging biologics targeting TSLP indicated potential for broader therapeutic applications in addressing allergic and immunological facets of CSU.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further research by Hashimoto et al [39] suggested TSLP's involvement in CSU's pruritic symptoms through basophil activation, extending its impact to sensory mechanisms within the disease. Observations by Treudler and Simon [40] on emerging biologics targeting TSLP indicated potential for broader therapeutic applications in addressing allergic and immunological facets of CSU.…”
Section: Discussionmentioning
confidence: 99%
“…However, contrasting evidence by Metz et al [41] regarding TSLP levels in CSU necessitated additional research to resolve discrepancies in cytokine profiles and their implications for clinical manifestations and QoL in CSU patients. Collectively, these insights [36][37][38][39][40][41] called for an integrated approach to CSU therapy that considered TSLP's multifaceted role in the immune response, advocating for refined strategies in patient care and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical studies will allow to better characterize these allergens, and diagnostic as well as therapeutic measurements have to be installed. Acute therapeutical interventions will follow current anaphylaxis guidelines, and possibilities for allergen immunotherapy have to be investigated [1,85].…”
Section: Discussionmentioning
confidence: 99%